(untitled) (European Journal of Pure and Applied Mathematics, 2012)
In this paper we study the stability concepts for set differential equations involving causalÂ operators with memory by considering initial functions as a Hukuhara difference of two functions. ThisÂ will enable to obtain results parallel to ordinary differential equations with delay.